Combining environmentally and economically sustainable dairy and beef production in Sweden. (September 2017) - Hessle, Anna; Bertilsson, Jan; Stenberg, Bo; Kumm, Karl-Ivar; Sonesson, Ulf
Abstract: To achieve a more sustainable food sector, a supply chain approach is needed. In this study, experts in different areas along supply chains co-operated in an interactive process to define future environmentally sustainable supply chains of milk and beef. The basis was to use existing techniques, to have production performance corresponding to the best quartile of today and to consider other sustainability aspects, such as economics. The work resulted in concrete descriptions of alternative product chains for delivered milk and beef. To also permit concrete descriptions of the latter part of the product chains, two consumer-packed end products were selected for monitoring, namely fresh milk and sirloin steak. The production systems investigated comprised cropping, livestock production, industrial processing and production, logistics, packaging and wastage and distribution, but not retailers or consumers. The study area was a Swedish county and the reference level was its production of milk and beef in 2012. The future product chains were assumed to deliver the same amounts of commodities as in 2012, but with reduced environmental impact. Primary production was required to be at least as profitable as today. Beside description of the current situation, three alternative scenarios were created, focusing on delivery of ecosystem services, plant nutrient circulation and minimising climate impact, respectively. Life cycle assessments were performed for these four scenarios (reference plus three alternative scenarios) for single-product chains and county-wide. Furthermore, production costs in primary production were calculated for the four scenarios. The results revealed great potential to reduce the negative environmental impact of Swedish dairy and beef production at current volumes, irrespective of whether ecosystem services, plant nutrient circulation or climate impact is in focus. The single most important factor for decreased environmental impact for livestock production was increased production efficiency. Measures in agriculture, especially concerning feeds, were critical, but actions in processing and distribution also contributed. All alternative scenarios resulted in lower production costs than at present. It was obvious that as dairy and beef systems are connected, the potential for their environmental improvement must be analysed together. In conclusion, increased efficiency can decrease the negative environmental impact of Swedish cattle production and also reduce costs to the farmer. Highlights: Swedish cattle production can improve both environmentally and economically. Increased production efficiency results in improved environment and lower costs. A common analysis of environmental impact is needed for dairy and beef production.